Isolation and Characterisation of Bacteriophages infecting Klebsiella pneumoniae from Sewage Samples in Sarawak, Malaysia - Paran, Andrea Ken (2020)
A group of nosocomial multidrug-resistant pathogens that posed threats to immunocompromised patients have previously been referred to by the acronym ESKAPE. The ESKAPE pathogens which include Gram-negative Klebsiella pneumoniae are considered a great threat, due to the emergence of strains that are resistant to all or most available antibiotics. Misuse and extensive consumption of broad-spectrum antibiotics in hospitalised patients have allowed the evolution of drug-resistant bacterial strains by producing defense mechanisms such as extended-spectrum β-lactamases and diverse aminoglycoside-inactivating enzymes. Many of these strains are highly virulent and exhibit a strong tendency to propagate. In this study, five lytic Klebsiella bacteriophages namely ɸKPaV03, ɸKPaV04, ɸKPaV08, ɸKPaV10, and ɸKPaV12 were isolated from domestic sewage at Universiti Malaysia Sarawak (UNIMAS) and characterised based on their biological properties, including bacteriophage morphology, host range, growth curve, bacteriophage multiplicity of infection (MOI) and structural protein composition. These bacteriophages have large burst size with high titer assay between 10^8 – 10^12 pfu / mL and were predominantly stable under 4 D.C. Two among the five bacteriophages were capable of efficiently lysing more than five Klebsiella pneumoniae strains out of 18 clinical and community-acquired isolates from Borneo Medical Centre (BMC) and students of UNIMAS, respectively. These bacteriophages exhibit several properties indicative of potential utility in phage cocktails and phage-antibiotic synergy (PAS) approach.